2014
DOI: 10.1088/1748-9326/9/6/064027
|View full text |Cite
|
Sign up to set email alerts
|

Emission factor of ammonia (NH 3 ) from on-road vehicles in China: tunnel tests in urban Guangzhou

Abstract: Ammonia (NH 3 ) is the primary alkaline gas in the atmosphere that contributes to formation of secondary particles. Emission of NH 3 from vehicles, particularly gasoline powered light duty vehicles equipped with three-way catalysts, is regarded as an important source apart from emissions from animal wastes and soils, yet measured emission factors for motor vehicles are still not available in China, where traffic-related emission has become an increasingly important source of air pollutants in urban areas. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
45
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 95 publications
(52 citation statements)
references
References 62 publications
6
45
1
Order By: Relevance
“…The tunnel is 1238.5 m in length with a 721 m flat underwater section. A schematic diagram of the tunnel is given by Liu et al (2014) and Zhang et al (2015). The tunnel's ventilation system was not operated during our study, and therefore in the tunnel bore selected for our test the air flow resulted entirely from the southbound vehicle traffic.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The tunnel is 1238.5 m in length with a 721 m flat underwater section. A schematic diagram of the tunnel is given by Liu et al (2014) and Zhang et al (2015). The tunnel's ventilation system was not operated during our study, and therefore in the tunnel bore selected for our test the air flow resulted entirely from the southbound vehicle traffic.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…These results, along with the fact that urban Beijing has a higher relative on-road vehicle density and almost no agricultural activity, suggest that NH 3 emission and transport from local traffic were the main contributors to high urban NH 3 concentrations. Based on a mileage-based NH 3 emission factors of 28 ± 5 (assumed as the lower limit; Chang et al, 2016) and 230 ± 14.1 mg km −1 (assumed as the upper limit; Liu et al, 2014) for light-duty gasoline vehicles, a population of 5.61 million vehicles (average mileage 21 849 km vehicle −1 yr −1 ) in Beijing would produce approximately 3.4-28 kt NH 3 in 2015, which likely declined by up to 4.7-38 t NH 3 day −1 during the Parade Blue period given that the traffic load decreased by half with the implementation of the odd-and-even car ban policy. For accurately determining NH 3 emissions, however, further study of NH 3 emission factors for vehicles and other sources is warranted.…”
Section: Impact Of Traffic Nh 3 Emission On Urban Nh 3 Concentrationmentioning
confidence: 99%
“…Recent tunnel studies indicated that emissions from light-duty gasoline vehicles (LDGVs) are also an important source of NH 3 [21][22][23][24][25]. Nordin et al [26] found that SOA formed from the exhaust of idling gasoline vehicles could be 1-2 orders of magnitude higher than POA.…”
Section: Introductionmentioning
confidence: 99%